Effect of attitude on religious appreciation among students in public university / Noor Zafarina Mohd Fauzi ... [et al.] - Mohd Fauzi, Noor Zafarina; Mohd Muhaimin, Mursyidah; Othman, Nurul 'Aliyana; Ab Malek, Muhammad Nur Izan; Mohamed Zukri, Shamsunarnie (2021)
Islam is an official religion Malaysia and despite being an Islamic country, the number of youth involved in social problems such as drugs abuse, pre-marital sex has led to the increasing rate of child abortion and even involvement in terrorism. Youths are the important asset of the country since they will lead the country someday. Although born and raised in Islamic education, theyare still interested in getting involved in social problems. There are fewaims of this study and the first is to determine the significance and direct effect of attitude towards religious appreciation. Next is to identify the factors that contribute towards attitude namely peers, family, education and environment. Besides that, the intention of this study is to identify the factors that influence religious appreciation namely faith, worship and moral values. A total of 244 students from one public university in Kelantan were randomly selected by using stratified random sampling technique. Questionnaire was used to collect the data and the results were analysed using Structural Equation Model (SEM) by applying Analysis of Moment Structure (AMOS) while descriptive statistics were derived from Statistical Package Software (SPSS). The findings of the study revealed that there is a significant and direct effect between attitude (β= 0.516, p<0.001) and religious appreciation. Moreover, peers, family, education and environment are the components of attitude. Meanwhile, the factors contributing to religious appreciation are faith, worship and moral values. Therefore, students' attitudes need to be strengthened to produce youths who appreciate religion.